Le désir de langue. Les dimensions poétique et politique de la diglossie dans le roman « Le jardin de verre » de Tatiana Țîbuleac - Cristina Hermeziu (Swedish Journal of Romanian Studies, 2021)
Still relevant today via mobility and the multicultural environment as the constitutive elements of our globalized societies, the reflections around “the cumbersome problem of the genius of languages” (Cassin 2016) join and enrich the question of living together and building oneself. In the field of literature or human sciences, the thought of the practice of languages in a situation of diglossia has forged an imaginary which often connects the passage from one language to another to a balance of power and a tension of identity. We propose an analysis of the symbolic values of the dilemma between the Romanian language and the Russian language which is at the heart of the diegesis of the novel Grădina de sticlă [The Glass Garden] by Tatiana Țîbuleac. Published in Romanian by Éditions Cartier de Chișinău and translated into several languages, including French and Spanish, the book was awarded the European Union Prize for Literature in 2019. The fictional world and the language of writing describe a symbolic abyss: the author describes in Romanian the fight with the Russian of a Moldovan orphan who is trying to rebuild herself between the two languages. In a very colorful style, the novel deploys a po(ï)etics of “between”, which also has a political dimension.